RACE DIVERSITY AND COMPLEXITY IN POPULATIONS OF THE SORGHUM ANTHRACNOSE FUNGUS Colletotrichum graminicola - CASELA, CARLOS ROBERTO; SANTOS, FREDOLINO GIACOMINI; FERREIRA, ALEXANDRE DA SILVA (International Journal of Maize & Sorghum, 2010)
The phenotypic diversity of the sorghum anthracnose fungus Colletotrichum graminicola, C. graminicola. was analyzed through virulence on 10 sorghum lines. Isolates of the pathogen were obtained from three locations of severe anthracnose epidemics: Sete Lagoas (MG), Pelotas (RS), and Cravinhos (SP). Populations were compared through the Shannon diversity index and through a pathogenicity association coefficient (PAC) and a virulence association coefficient (VAC). Despite high values obtained, a large portion of information on the phenotypic diversity in all populations was lost due to deviation from the ideal frequency of 0.5 for virulence to each sorghum genotype. Six two-line and 11 three-line combinations were identified with low virulence association in the pathogen population. Lines CMSXS215B, CMSXS116, and CMSXS227R, present in all combinations with high PAC and low VAC, were identified as potential sources for stable and durable resistance to.